2019
DOI: 10.1039/c9ra00344d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of antidiabetic, bactericidal, and antitumor activities of MEL@AgNPs, MEL@ZnONPs, and Ag–ZnO/MEL/GA nanocomposites prepared by using MEL and gum arabic

Abstract: MEL@AgNPs, MEL@ZnONPs, and Ag–ZnO/MEL/GA nanocomposites were successfully prepared by using mannosylerythritol lipids (MEL) and gum arabic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…The SEM images confirm the attachment of ZnO NPs on the bacterial cell surface and the subsequent disturbance to the integrity of bacterial cell membrane, which resulted in cell wrinkling and distortion. Similar findings were reported in the treatment of ZnO NPs, which caused cell membrane damage in E. coli ( Arakha et al, 2015 ), cell shrinkage in E. coli and S. enterica ( Bakur et al, 2019 ), membrane distortion, membrane blebbing, and leakage of cellular contents of E. coli and P. mirabilis ( Maruthupandy et al, 2018 ).…”
Section: Resultssupporting
confidence: 83%
“…The SEM images confirm the attachment of ZnO NPs on the bacterial cell surface and the subsequent disturbance to the integrity of bacterial cell membrane, which resulted in cell wrinkling and distortion. Similar findings were reported in the treatment of ZnO NPs, which caused cell membrane damage in E. coli ( Arakha et al, 2015 ), cell shrinkage in E. coli and S. enterica ( Bakur et al, 2019 ), membrane distortion, membrane blebbing, and leakage of cellular contents of E. coli and P. mirabilis ( Maruthupandy et al, 2018 ).…”
Section: Resultssupporting
confidence: 83%
“…However, their UV-C mediated counterparts showed slightly less inhibition. Bakur et al [58] reported similar level of anti-diabetic activities of biogenic bimetallic Ag-ZnONPs in a concentration-dependent manner. Our study shows the promise of green NPs as an effective drug in managing diabetes (Figure 14A).…”
Section: Anti-diabetic and Anti-glycation Activities Of Green Synthesized Agnps Znonps And Bimetallic Ag-znonpsmentioning
confidence: 82%
“…Our previous researches also revealed that MEL-A has significantly inhibited the growth of Bacillus cereus [12] and Staphylococcus aureus [13] . Expect for its intrinsic capacity, MELs have been a key part of nanoparticles as emulsifier, exhibiting potent inhibitive effect on pathogens [30] , [31] , [32] . However, the abuse of antibiotics resulted in the emergence of methicillin-resistant Staphylococcus aureus (MRSA), which can survive in severe environment and convey a novel challenge to anti-infective treatments [33] .…”
Section: Discussionmentioning
confidence: 99%